Does the neighborhood food environment contribute to ethnic inequalities in fast-food intake? findings from the ORiEL study - Shareck, Martine (Prev Med Rep, 2019)
The neighborhood food environment may contribute to ethnic inequalities in diet. Using data from 1389 participants in the Olympic Regeneration in East London (UK) study we assessed whether ethnic inequalities in neighborhood availability of fast-food restaurants mediated and/or modified ethnic inequalities in fast-food intake in 13–15 year-old adolescents. We compared the proportion of high fast-food consumers across “White UK”, “Black”, and “South Asian” ethnic categories. We used Poisson regression with robust standard errors to assess direct and indirect effects (mediation analysis) and risk ratios of high fast-food intake by ethnic category and fast-food restaurant availability level (effect measure modification analysis). There were ethnic inequalities in high fast-food intake, with risk ratios in adolescents of Black and South Asian background of 1.53 (95% CI: 1.25, 1.87) and 1.71 (95% CI: 1.41, 2.07) respectively compared to White UK participants. We found no evidence of a mediating effect by fast-food restaurant availability, but found some evidence of effect measure modification: ethnic inequalities in fast-food intake were largest in neighborhoods lacking fast-food restaurants, and narrowed as availability increased. Future research should explore why ethnic minorities are more likely to be high fast-food consumers than the majority ethnic group, especially when fast-food restaurant availability is lowest.